Subjective quality of life in war-affected populations - Matanov, Aleksandra (Array, 2013)
Exposure to traumatic war events may lead to a reduction in quality of life for many years. Research suggests that these impairments may be associated with posttraumatic stress symptoms ; however, wars also has a profound impact on social conditions. Systematic studies utilising subjective quality of life (SQOL) measures are particularly rare and research in post-conflict settings is scarce. Whether social factors independently affect SQOL after war in addition to symptoms has not been explored in large scale studies. War-affected community samples were recruited through a random-walk technique in five Balkan countries and through registers and networking in three Western European countries. The interviews were carried out on average 8 years after the war in the Balkans. SQOL was assessed on Manchester Short Assessment of Quality of Life - MANSA. We explored the impact of war events, posttraumatic stress symptoms and post-war environment on SQOL. We interviewed 3313 Balkan residents and 854 refugees in Western Europe. The MANSA mean score was 4.8 (SD = 0.9) for the Balkan sample and 4.7 (SD = 0.9) for refugees. In both samples participants were explicitly dissatisfied with their employment and financial situation. Posttraumatic stress symptoms had a strong negative impact on SQOL. Traumatic war events were directly linked with lower SQOL in Balkan residents. The post-war environment influenced SQOL in both groups: unemployment was associated with lower SQOL and recent contacts with friends with higher SQOL. Experiencing more migration-related stressors was linked to poorer SQOL in refugees. Both posttraumatic stress symptoms and aspects of the post-war environment independently influence SQOL in war-affected populations. Aid programmes to improve wellbeing following the traumatic war events should include both treatment of posttraumatic symptoms and social interventions.